The influence of Er3+ doping on the structural and optical properties of CeO2 thin films grown by PED - Tatar, B.; Gokdemir, F. P.; Pehlivan, E.; Urgen, M. (ELSEVIER SCIENCE BV, 2013)
Erbium doped CeO2 thin films were deposited on both Corning glass substrates and indium doped tin oxide (ITO) coated glass substrates by pulsed e-beam deposition (PED) method at room temperature. Structural features of Er doped CeO2 thin films were studied with X-ray diffraction (XRD) and micro-Raman spectra. The XRD patterns of all films showed polycrystalline nature and cubic crystalline structure. Raman active peaks for both undoped CeO2 and Er doped CeO2 films were determined at similar to 465 cm(-1). The Raman shift observed in this study can also be assigned to Raman active modes of CeO2 that are shifted from the original position due to different doping concentration. The optical properties of CeO2 films and Er doped CeO2 films, which were determined from transmittance and reflectance measurements at room temperature, were very similar in character. The refractive indices and extinction coefficients, which were calculated from 3.5 to 1.25 eV (300-1000 nm), were between 1.5-3 and 0.05-0.2, respectively. The optical band gaps were deduced from the absorption coefficient according to solid band theory. The electrochromic measurements revealed that 2% Er doped CeO2 films grown on ITO + WO3 substrates had highest charge density compared to the other samples. Long-time cyclic voltammetry (CV) and chronoamperometry (CA) measurements were carried out to investigate the stability of this film. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Electrochromic materials; CeO2 crystal structure; Er doping; Optical properties; Electrochemical properties; CHEMICAL-VAPOR-DEPOSITION; CERIUM OXIDE; DOPED CERIA; MICROSTRUCTURE; PERFORMANCE; PRECURSORS; COATINGS; APATITE; Chemistry; Materials Science; Physics